The Impact of Digital Competence and Organizational Climate on Employee Performance: An Analysis of the Mediating Role of Work Motivation at UPT PLN Malang - Marli; Dwi Danesty Deccasari (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze the influence of Organizational Climate on Employee Performance with Work Motivation as a mediating variable at UPT PLN Malang. The main hypothesis states that Organizational Climate has a positive direct and indirect effect through Work Motivation on Employee Performance. The study used a quantitative design with the SEM-PLS approach that is able to handle latent variables and data that are not necessarily normally distributed. A sample of 98 employees was randomly selected stratified by division and position. Data were collected through a structured questionnaire that has been tested for validity and reliability. The analysis focused on evaluating the measurement model and the structural model using bootstrapping to test the significance of the paths. The results indicate that Organizational Climate has a significant positive effect on Work Motivation and Employee Performance, with Work Motivation partially mediating the relationship. The findings emphasize the importance of creating a conducive organizational climate and increasing motivation for optimizing employee performance. Practical implications include the development of motivational training, effective communication, and a trust-based management system at UPT PLN Malang. Further studies are recommended using longitudinal data to strengthen causal findings.